Museum collections are the key to studying lemurs' diet: gastrointestinal morphology of Cheirogaleus major. Issue 5 (4th July 2018) - Buerki, Sven; Portela Miguez, Roberto
Abstract : This study reports the first description of the gastrointestinal (GIT) morphology of a lemur species ( Cheirogaleus major É. Geoffroy, 1812) of the family Cheirogaleidae using a museum collection deposited at the Natural History Museum, London. Knowledge on GIT morphology is the key to assessment of the diet of animals, especially those that are highly threatened. Several studies predicted the demise of lemurs (>100 species representing 20% of the world's primate diversity) by 2080 unless the conservation community acts quickly. In this context, museum collections could provide valuable evidence on the biology of lemurs to underpin conservation protocols. The feeding ecology of the omnivorous Cheirogaleus major is poorly known due to its secretive periods of hibernation and daily torpor, nocturnal activity and solitary foraging habit. To better understand the biology of C. major, we described and compared its GIT morphology with those of six other species for which we have published data, especially the frugivore taxa ( Eulemur coronatus Grey, 1842 and Varecia variegata Kerr, 1792). Our findings showed that C. major has a GIT morphology similar to those of E. coronatus and V. variegata . This is especially the case because of its caecum, which is short and only slightly sacculated suggesting that it is not suitable for microbial breakdown of plant cell wall (unlike those of Propithecus species, Lemur catta, and Hapalemur griseus ). This result is in line with ecological studies suggesting that C. major obtains its protein and carbohydrate intake from fruits and to some extent arthropods and not from the digestion of leaves as previously hypothesized. In light of this new evidence, conservation programmes should account for both the lemur and its associated flora. Overall, this study demonstrates the unique potential of museum collections to study the nutritional ecology of threatened animals and their potential role in supporting conservation.